Mechanical properties and fractographic analyses of FeCo-2V alloy heat-treated around order-disorder transition temperature - Li, Zhiqiang (2023)
The effect of heat treatment on the mechanical properties of FeCo-2V alloy was investigated at temperatures slightly above and below its order-disorder transition point with varied holding times and cooling rates. The fracture surface, grain size, and recrystallized microstructure were characterized by SEM and EBSD. The correlation between yield strength and microstructural features was analysed. Yield strength was found to decrease with the elevation of heating temperature, extension of holding time, and decrease in cooling rate. Fast cooling significantly improved the mechanical strength and ductility. The quenched samples exhibited microscopically ductile fracture features with shallow dimples on the fractured surface, while the slow-cooled ones displayed brittle microscopic fracture features, regardless of the heating temperature and holding time. The yield strength follows two separate Hall-Petch relationships for samples dominantly in the ordered and disordered states. Our analyses reveal that the mechanical strength of FeCo-2V alloy is mainly controlled by the grain size, thus it is important to regulate the grain recrystallization and growth during the heat treatment process.